Revealing Iʿjāz al-Qur’an: Analysis of the Strength of Evidence in the Makiyah Polemic Verses - Ahmad Lutfi (Dialogia, 2026)
Classical scholarship has predominantly located the i‘jāz al-Qur’an (the inimitability of the Qur’an) in its linguistic excellence, scientific allusions, and foreknowledge of the unseen. Such approaches, however, have paid limited attention to the Qur’an’s polemical discourse as a possible locus of i‘jāz. This article proposes an alternative perspective by examining the inimitability of the Qur’an through the argumentative and moral force embedded in its polemical verses. It addresses three questions: why i‘jāz appears within Qur’anic polemics, how these verses affected the Meccan audience, and in what ways the Qur’an’s argumentative structure functioned as a form of i‘jāz in the socio-historical context of Mecca. This study employs qualitative textual analysis based on primary sources consisting of Meccan surahs and selected sīrah literature, complemented by secondary scholarship from both Muslim and Orientalist traditions. The analysis is conducted through a contemporary interpretive framework integrating Muḥammad ‘Ābid al-Jābirī’s theory of Arab reason and Abu Hilal al-‘Askarī’s conception of i‘jāz. The study argues that the inimitability of the Qur’an cannot be reduced solely to aesthetic or epistemic dimensions but also resides in its capacity to construct compelling and irreducible arguments against the opponents of prophethood while simultaneously generating new forms of communal solidarity. The findings indicate that the Qur’an emerged within a context of socio-economic inequality and exercised transformative power by challenging established authority through a moral discourse grounded in values that were already recognized within the religious consciousness of Meccan society. This article contributes to contemporary Qur’anic studies by advancing a moral-argumentative model of i‘jāz, demonstrating that the Qur’an’s polemical discourse constitutes a distinct mode of Qur’anic inimitability.